ENT600: Icare Medical Resources / Airin Fatehah Aziz … [et al.] - Aziz, Airin Fatehah; Yahaya, Nurul Suryanie; Abd Latif, Siti Zarifah; Roslan, Nurul Azra; Zaki, Aina Zahirah (2018)
This study aims to determine the issue that faced by the company that selling health and rehabilitation appliances named as ICare Medical Resources located at Perlis. Based on the interviewing session the findings related to the timed consumed due, to manual filing system become the highlighted issues as well as the absence of delivery system provided that lead to limitation to the customer to received their purchased items properly. Lastly, the issues that should be emphasize in this study was related to the limitation of storage space provided causes the product not properly arranged and display to the customer. Therefore, these issues should be managed meticulously in order to maintained and increase the business performance of this company by improving their services as well as the management system.